Determinantes da dolarização financeira em economias emergentes e desenvolvidas - Fabricio de Assis Campos Vieira (2012)
This work explores the persistence of financial dollarization in a group of 79 economies with different levels of development. Our first hypothesis is that a high level of domestic debt combined with default risk explains this persistence, even after a decline in inflation rates. Using the generalized method of moments (GMM) in a panel data analysis, our results show that inflation risks caused by increasing probability of default account for financial dollarization more than inflation rate itself. After the decrease in inflation rates, the foreign currency-denominated deposits remain large because of the high debt-to-GDP ratios, particularly in speculative-grade economies. High internal public indebtedness leads to expectations of default. Dollarization is a rational response to the future inflation associated with investors expectations of default observed in highly indebted economies. The second hypothesis postulates that financial dollarization is related to shortage of foreign resources. Changes in external capital flows have distinct effects on the liquidity preference in hedge economies vis-à-vis speculative economies. For these economies the demand for foreign currency is stronger in scarcity periods. The results showed that a lower availability of foreign resources to the most vulnerable economies (speculative economies) is responsible for an increase in the degree of liquidity preference of their agents. Increases in liquidity preference lead to more foreign currency deposits being held as a form of hedging, specially in speculative economies.